The adaptation potential of water law in Canada: changing existing water use entitlements. Issue 3 (3rd April 2019) - Curran, Deborah
ABSTRACT: Recommendations to extend water law reform to include the adaptation of existing water entitlements goes against a basic principle of water law: to provide security of tenure to water authorization holders so they can rely on a specific volume of water. This paper evaluates how well subnational water law in Canada permits adaptive management to address existing water authorizations. With some laws allowing changes based on new scientific information, the public interest or planning, possibilities for adaptive water law in Canada arise that are instructive for other jurisdictions.